Assessment of the Burden of Serious Human Fungal Infections in Malaysia - Rukumani Devi Velayuthan; Chandramathi Samudi; Harvinder Kaur Lakhbeer Singh; Kee Peng Ng; Esaki M. Shankar; David W. Denning (Innovations in Microbiology and Biotechnology Vol. 4, 2022)
The present study expected to provide a better perspective of our understanding of the global distribution of serious human fungal infections, serve as a reference for future investigations, and will contribute to the improvement in the public health aspects of fungal infections in the region. Fungal infections (mycoses) are likely to occur more frequently as ever-increasingly sophisticated healthcare systems create greater risk factors. There is a paucity of systematic data on the incidence and prevalence of human fungal infections in Malaysia. We conducted a comprehensive study to estimate the burden of serious fungal infections in Malaysia. Our study showed that recurrent vaginal candidiasis (>4 episodes/year) was the most common of all cases with a diagnosis of candidiasis (n = 501,138). Oesophageal candidiasis (n = 5850) was most predominant among individuals with HIV infection. Candidemia incidence (n = 1533) was estimated in hospitalized individuals, some receiving treatment for cancer (n = 1073), and was detected also in individuals admitted to intensive care units (ICU) (n = 460). In adults with asthma, allergic bronchopulmonary aspergillosis (ABPA) was the second most common respiratory mycoses noticed (n = 30,062) along with severe asthma with fungal sensitization (n = 39,628). Invasive aspergillosis was estimated in 184 cases undergoing anti-cancer treatment and 834 ICU cases. Cryptococcal meningitis was diagnosed in 700 subjects with HIV/AIDS and Pneumocystis jirovecii pneumonitis (PCP) in 1286 subjects with underlying HIV disease. The present study indicates that at least 590,214 of the Malaysian population (1.93%) is affected by a serious fungal infection annually. This problem is serious enough to warrant the further epidemiological studies to estimate the burden of human fungal infections in Malaysia.